Legal Certainty in Investor Liability for Environmental Rehabilitation: The Role of Environmental Cost Allocation in the Coal Mining Sector - Galenso, Vidi; Suganda, Atma; Achmad Darodjat, Tubagus (CV. Era Digital Nusantara, 2025)
The coal mining sector contributes significantly to the Indonesian economy, but also leaves serious environmental impacts. This research aims to examine the legal certainty of investor responsibility in environmental restoration through an environmental costing mechanism. The research method used is normative juridical with statutory and conceptual approaches. The results show that there are discrepancies between legal norms and their implementation in the field. Investor responsibility is often not carried out substantially, and there is no binding long-term accountability system after the expiry of the mining licence. This research provides novelty by proposing regulatory reconstruction based on the principles of strict liability, environmental justice, and digital-based transparency. In conclusion, it is necessary to strengthen the environmental law system that is more substantial and oriented towards ecological sustainability and intergenerational justice.